Fungal Infection of the External Auditory Canal or Otomycosis in Western Libya - Amal Enbaya; Alya Duzan; Taher El Masri (AlQalam Journal of Medical and Applied Sciences, 2024)
Otomycosis has typically been described as fungal infection of the external auditory canal (EAC). The aim of the present work is to report on fungi incremented in this type of infection. The study was conducted at the department of biology, faculty of education, at university of Tripoli. The study was held from June to August 2023 at 30 pretreatment patients of the age group (15 -63) of both sex, males (13) and females (17), attending the outpatient department of Otorhinolaryngology at the two main Medical Centers in Tripoli-Libya, University Tripoli Hospital and Central Tripoli Hospital. External auditory canal exudates were collected, swabs in each patient were observed by direct microscopic examination and cultured in Sabouraud Dextrose Agar (SDA) medium. Using classical standard identification keys at the species level, Aspergillus with Aspergillus niger and Candida with Candida albicans species were reported as the most dominant isolates. يوصف فطريات الأذن عادة بأنه عدوى فطرية للقناة السمعية الخارجية، الهدف من هذا الدراسة هو الإبلاغ عن الفطريات المتزايدة في هذا النوع من العدوى. أجريت الدراسة بقسم الأحياء بكلية التربية- طرابلس ليبيا. خلال الفترة من يونيو إلى أغسطس 2023 ،على 30 مريضًا من الفئة العمرية (15 - 63) من كلا الجنسين،(13) ذكور و (17) إناث ، من المرضي المراجعين للعيادة الخارجية لقسم أمراض الأنف والأذن والحنجرة(ENT) في المركزين الطبيين الرئيسيين في طرابلس - ليبيا، هما مستشفى جامعة طرابلس التعليمي و مستشفى طرابلس المركزي . تم جمع العينات وذلك بأخذ مسحات من إفرازات القناة السمعية الخارجية من كل مريض ثم زراعة في وسط (SDA)، ثم تم الفحص المجهري المباشر للفطريات النامية ، وباستخدام مفاتيح التعريف القياسية الكلاسيكية على مستوى الأنواع تم عزل عدة أنواع من الفطريات منها التابعة لجنس Aspergillus ابرزهاAspergillus niger ، و عزل انواع من Candida ابرزها Candida albicans حيت كانت أكثر العزلات السائدة.